Development of culture-based counseling communication skills module - Wan Chalidaziah; Nengsih Nengsih; Sabrida M. Ilyas (Counseling and Humanities Review, 2022)
This study aims to develop guidance and counseling modules to improve culture-based counseling communication skills for guidance and counseling students to fulfill the basic ability requirements for communication skills in culture-based counseling that must be mastered, as well as to describe the level of its application by lecturers who take basic courses of counseling communication in units college guidance and counseling services. The research method uses the ADDIE Research and Development model (Analyze, Design, Development, Implementation, and Evaluation). The research was conducted by testing research products in the form of modules and FGDs. Data were analyzed using descriptive and inferential analysis. The results showed that the culture-based counseling communication skills module was in the very proper category with an average score of 4.80 and an usability test result of 4.33, which means that the designed module product can be used and passed the usability test by experts. Furthermore, the culture-based counseling communication skills module can be used in learning for guidance and counseling students.